Transformasi Hijau: Mengoptimalkan Peran Strategis dalam Keberlanjutan Lingkungan Perusahaan - Fadia Rahmadhini Hartama; Shinta Permata Sari (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Sustainability reporting serves as an essential medium for communication their social and environmental responsibilities to the public and stakeholders. This study aims to analyze the effect of Green Accounting, Environmental Performance, ISO 14001 Certification, and Media Disclosure on Sustainability Report Disclosure in consumer non-cyclicals companies listed on the Indonesia Stock Exchange in 2022–2024. This study employs a quantitative approach using secondary data obtained through documentation methods from companies financial statements and sustainability reports. The sample use a purposive sampling technique, resulting in a final total of 96 data units. Data analyze using multiple linear regression with the assistance of SPSS version 27. The reveal that Green Accounting has no effect on Sustainability Report Disclosure. Meanwhile, Environmental Performance, ISO 14001 Certification, and Media Disclosure have effect on Sustainability Report Disclosure. These results support the Legitimacy Theory and Stakeholder Theory, indicating that companies seek to gain social legitimacy and meet public expectations by enhancing transparency and presenting more comprehensive sustainability reporting.